Penetapan Tanah Terlantar Sebagai Bentuk Perlindungan dan Kepastian Hukum dalam Penertiban Kawasan Tanah Terlantar - Zarbiyani, Farhan; Sudiro, Amad (Universitas Ekasakti, 2023)
The purpose of writing this article is to find out how the form of legal protection and legal certainty over the determination of abandoned land as a form of controlling abandoned land areas. This article uses normative legal research, with statute approach and conceptual approach and descriptive qualitative research analysis with deductive thinking method. The form of legal protection for the community against the determination of abandoned land is through the utilisation of abandoned land by the government which is a strategic stage and the mechanism must be able to ensure that efforts to curb abandoned land must be returned to the greatest prosperity of the people through the process of determining abandoned land that applies the values of the General Principles of Good Governance and in accordance with statutory regulations, starting from the Basic Agrarian Law, Government Regulation No. 18 of 2021 concerning Management Rights, Land Rights, Flat Housing Units, and Land Registration, Regulation of the Minister of Agrarian Affairs and Spatial Planning, Head of the National Land Agency No. 20 of 2021 concerning Procedures for the Ordering and Utilisation of Abandoned Areas and Land, as a form of guarantee in providing legal certainty in the issuance of the determination of abandoned land.